O075 Antithrombotic therapy for aortic and peripheral artery aneurysms: a systematic review and meta-analysis. (22nd July 2022) - Wong, KHF; Zlatanovic, P; Bosanquet, DC; Aboyans, V; Saratzis, A; Kakkos, SK; Hinchliffe, RJ; Twine, CP
Abstract: Introduction: The role of antithrombotic agents in aneurysm progression and outcomes following surgical or endovascular intervention is unclear. Methods: A systematic review and meta-analysis was performed. Medline, Embase, and CENTRAL databases were searched. Randomised-controlled trials and observational studies investigating the effect of antithrombotic therapy on clinical outcomes for patients with aortic or extracranial peripheral arterial aneurysms were included. Aneurysm growth rate, major adverse cardiovascular or limb events, mortality, endoleaks, re-intervention rates, and other outcomes were captured. Results: Fifty-seven studies involving 121, 451 patients were included (26 antiplatelets, 12 anticoagulants, 16 any antithrombotic agent(s), 2 intra-operative heparin). Aspirin reduced growth rates of aortic aneurysms under surveillance (mean difference -0.9mm/y, 95%CI -1.74 to -0.07, p=0.03; GRADE certainty: moderate). For aortic aneurysms undergoing intervention, anti-thrombotics increased 30-day mortality (odds ratio [OR] 2.30, 95%CI 1.51 to 3.51, p<0.001; GRADE certainty: moderate). Antiplatelets reduced long-term all-cause mortality (hazard ratio [HR] 0.84, 95%CI 0.76 to 0.92, p<0.001; GRADE certainty: moderate), whilst anticoagulants increased this risk (HR 1.64, 95%CI 1.14 to 2.37, p=0.008; GRADE certainty: very low). Anticoagulants increased incidence of endoleaks under 3 years, and re-intervention rates (p<0.05 for all). Antithrombotic agents did not significantly affect rupture rates in aortic aneurysms. Meta-analysis was not possible for ruptured aneurysms and popliteal aneurysms. Conclusion: There is moderate quality evidence that aspirin reduces aneurysm growth rates. Antiplatelet agents reduced all-cause mortality in aneurysms after intervention; whilst anticoagulants increased this risk, along with endoleaks and re-interventions. Well-designed trials are required to determine therapeutic benefits of antithrombotic agents for patients with aneurysms. Take-home message: Antiplatelets may have a role in reducing aneurysm growth rates and all-cause mortality; whilst anticoagulants are associated with increased mortality, endoleaks, and re-interventions. Well-designed trials are required to determine therapeutic benefits of antithrombotic agents for patients with aneurysms.